|
|
|
@ -3,6 +3,8 @@
@@ -3,6 +3,8 @@
|
|
|
|
|
The variables _state.quat_nominal(0) -> _state.quat_nominal(3) are the attitude quaternions |
|
|
|
|
The variable daYawVar is the variance of the yaw angle uncertainty in rad**2 |
|
|
|
|
See DeriveYawResetEquations.m for the derivation |
|
|
|
|
The gnerate autocode has been cleaned up with removal of 0 coefficient terms and mirroring of lower |
|
|
|
|
diagonal terms missing from the derivation script raw autocode output of C_code4.txt |
|
|
|
|
*/ |
|
|
|
|
|
|
|
|
|
// Intermediate variables
|
|
|
|
@ -20,15 +22,21 @@ SQ[3] = 0.5f * ((_state.quat_nominal(0)*SG[0]) + (_state.quat_nominal(1)*SG[2])
@@ -20,15 +22,21 @@ SQ[3] = 0.5f * ((_state.quat_nominal(0)*SG[0]) + (_state.quat_nominal(1)*SG[2])
|
|
|
|
|
// Variance of yaw angle uncertainty (rad**2)
|
|
|
|
|
const float daYawVar = TBD; |
|
|
|
|
|
|
|
|
|
// Add covariances for additonal yaw uncertainty to exisiting covariances.
|
|
|
|
|
// Add covariances for additonal yaw uncertainty to existing covariances.
|
|
|
|
|
// This assumes that the additional yaw error is uncorrrelated
|
|
|
|
|
P[0][0] += daYawVar*sq(SQ[2]); |
|
|
|
|
P[0][1] += daYawVar*SQ[1]*SQ[2]; |
|
|
|
|
P[1][1] += daYawVar*sq(SQ[1]); |
|
|
|
|
P[0][2] += daYawVar*SQ[0]*SQ[2]; |
|
|
|
|
P[1][2] += daYawVar*SQ[0]*SQ[1]; |
|
|
|
|
P[2][2] += daYawVar*sq(SQ[0]); |
|
|
|
|
P[0][3] += daYawVar*SQ[2]*SQ[3]; |
|
|
|
|
P[1][3] += daYawVar*SQ[1]*SQ[3]; |
|
|
|
|
P[2][3] += daYawVar*SQ[0]*SQ[3]; |
|
|
|
|
P[3][3] += daYawVar*sq(SQ[3]); |
|
|
|
|
P[0][0] += yaw_variance*sq(SQ[2]); |
|
|
|
|
P[0][1] += yaw_variance*SQ[1]*SQ[2]; |
|
|
|
|
P[1][1] += yaw_variance*sq(SQ[1]); |
|
|
|
|
P[0][2] += yaw_variance*SQ[0]*SQ[2]; |
|
|
|
|
P[1][2] += yaw_variance*SQ[0]*SQ[1]; |
|
|
|
|
P[2][2] += yaw_variance*sq(SQ[0]); |
|
|
|
|
P[0][3] -= yaw_variance*SQ[2]*SQ[3]; |
|
|
|
|
P[1][3] -= yaw_variance*SQ[1]*SQ[3]; |
|
|
|
|
P[2][3] -= yaw_variance*SQ[0]*SQ[3]; |
|
|
|
|
P[3][3] += yaw_variance*sq(SQ[3]); |
|
|
|
|
P[1][0] += yaw_variance*SQ[1]*SQ[2]; |
|
|
|
|
P[2][0] += yaw_variance*SQ[0]*SQ[2]; |
|
|
|
|
P[2][1] += yaw_variance*SQ[0]*SQ[1]; |
|
|
|
|
P[3][0] -= yaw_variance*SQ[2]*SQ[3]; |
|
|
|
|
P[3][1] -= yaw_variance*SQ[1]*SQ[3]; |
|
|
|
|
P[3][2] -= yaw_variance*SQ[0]*SQ[3]; |
|
|
|
|